Interventions that Address Institutional Child Maltreatment: An Evidence and Gap Map. (May 2023) - Finch, Meghan; Featherston, Rebecca; Chakraborty, Sangita; Bjørndal, Ludvig; Mildon, Robyn; Albers, Bianca; Fiennes, Caroline; Taylor, David J. A.; Schachtman, Rebecca; Yang, Taoran; Shlonsky, Aron
Purpose: This evidence and gap map collates evidence reporting on the effectiveness of interventions aimed to prevent, disclose, respond to, or treat child maltreatment occurring in institutional settings. Methods: A comprehensive and systematic literature search identified primary studies and systematic reviews meeting the review's eligibility criteria. Literature screening, data extraction and critical appraisals were undertaken independently by multiple reviewers. Data extracted and reported from the included studies included information about the institutional setting, target population, type of maltreatment, intervention type and outcomes. Results: Seventy-three studies were identified, including 11 systematic reviews and 62 primary studies. Overall, the methodological quality of the studies was low to moderate. Most evaluated curriculum-based interventions delivered in educational settings, primarily aimed at preventing sexual abuse. Fewer studies examined other institutional settings or intervention types. Conclusions: This review highlights a need for high-quality studies evaluating a more diverse range of interventions across more varied institutional contexts.